YOUTUBE: SEBUAH KAJIAN DEMOKRATISASI INFORMASI DAN HIBURAN - Alamsyah, Anggriani (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2021)
This paper aims to describe the position of mainstream audio-visual media which has been replaced by a digital platform, Youtube. YouTube has produced some famous people who have been 'untouched' by the mainstream media. The author obtained data and information from YouTube channels, literature and online news. In analyzing this phenomenon, the author uses three concepts: power, the democratization of information, and social media. The author concludes that this platform provides space for anyone to express and get advantages from democratizing information and entertainment. The control of information and entertainment is no longer in the hands of big media corporations but belongs to people like Andovi Da Lopez, Nessie Judge, Hansol, Budi “Epenkah Cupentoh” or even Jeromee who had never appeared on TV screens before.